Playing at acquisitions : behavioral option games - Smit, Han T. J., 1967-; Moraitis, Thras, 1963- (Princeton University Press, 2014)
It is widely accepted that a large proportion of acquisition strategies fail to deliver the expected value. Globalizing markets characterized by growing uncertainty, together with the advent of new competitors, are further complicating the task of valuing acquisitions. Too often, managers rely on flawed valuation models or their intuition and experience when making risky investment decisions, exposing their companies to potentially costly pitfalls. Playing at Acquisitions provides managers with a powerful methodology for designing and executing successful acquisition strategies. The book tack.